2004
DOI: 10.1111/j.0013-8703.2004.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition behaviour and patch‐time allocation in two aphid parasitoids exposed to deltamethrin residues

Abstract: Neurotoxic insecticides are widely used for crop protection. One consequence is that changes in behaviour can be expected in surviving beneficial insects because of an impairment of host perception and motor abilities. Under laboratory conditions, we studied the impact of deltamethrin, a pyrethroid, on the oviposition behaviour of two hymenopterous parasitoids of aphids, Aphidius matricariae (Haliday) and Diaeretiella rapae (McIntosh) (Hymenoptera: Braconidae). They both parasitize Myzus persicae (Sulzer) (Hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 42 publications
(43 reference statements)
3
35
0
2
Order By: Relevance
“…Upon host encounter, eVective detection of the host (e.g. aphid) occurs when 'antennal palpation' follows 'antennal contact' (Desneux et al 2004b) and is based on the physical and chemical cues acting at short range or by contact (Battaglia et al 2000). In our experiment, frequencies of 'antennal palpation' were always equal to or higher than frequencies of 'antennal contact', indicating that parasitoids easily detected M. persicae.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Upon host encounter, eVective detection of the host (e.g. aphid) occurs when 'antennal palpation' follows 'antennal contact' (Desneux et al 2004b) and is based on the physical and chemical cues acting at short range or by contact (Battaglia et al 2000). In our experiment, frequencies of 'antennal palpation' were always equal to or higher than frequencies of 'antennal contact', indicating that parasitoids easily detected M. persicae.…”
Section: Discussionmentioning
confidence: 47%
“…Although both species diVer in their behavioral responses to M. persicae on canola (Desneux et al 2004b), both appear well-adapted to this speciWc host-plant complex (Wilson and Lambdin 1987;Desneux et al 2005). In contrast, Aphidius ervi Haliday and A. colemani Viereck (Hymenoptera: Braconidae), both parasitoids of M. persicae that are abundant in European agricultural landscapes (Kavallieratos et al 2004;Lumbierres et al 2007), are respectively rarely found and not found at all to attack M. persicae in winter canola (Desneux et al 2006b;Desneux N. unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…maximum of 5 min or until successful oviposition) (Desneux et al, 2004). We compared these frequencies and the time until oviposition for the various aphid developmental stages using a non-parametric Kruskal-Wallis test.…”
Section: No-choice Assay Of Host Acceptancementioning
confidence: 99%
“…The results obtained by these authors draw attention to the fact that orientation and oviposition behaviours of parasitoids may be disturbed by pyrethroids, depending on the dose, the parasitoid experience and the type of behaviour. Conversely, the oviposition behaviour (both frequencies and behavioural sequences) of D. rapae and A. matricariae (Hymenoptera: Braconidae) on aphid-infested plants and patch-time allocation were not disturbed following exposure to deltamethrin residues (Desneux et al, 2004b), regardless of the dose. According to these authors the unexpected lack of effects after deltamethrin exposure can have two explanations: either the deltamethrin molecules did not alter the functions necessary for host-handling behaviour, or the surviving insects were less susceptible (reflecting differences in parasitoid vigour or in genetically determined susceptibility to pesticides).…”
Section: Oviposition Behaviourmentioning
confidence: 99%